$$\left( {\overline N ,Δ λ } \right)$$ - Salwa, Salwa; Aini, Qurratul; Switrayni, Ni Wayan (Jurnal Matematika, 2022)
Sequence s p aces is one of interesting to p ic of analysis research. Some of that are convergent and bounded sequence. In this  p a p er we define some releated BK s p aces  (????,?????)?, (????,?????), dan (????,?????)0  some characteristics releated to them. Moreover we determine  their ?-dual.